On the Expedience of Statutory Regulation of Fiduciary Transfer of Property in Serbia - Dudaš, Atila (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
No case of fiduciary transfer of property is explicitly governed by the effective Serbian law. Only the fiduciary assignment of claim is regulated in the Law on Obligations. One specific kind of fiduciary contracts is however frequently concluded, the fiduciary transfer of property as collateral. The case law is all but unanimous that such contracts are to be considered invalid (either entirely or partially), mainly because they infringe the prohibition of lex commissoria, although there are some decisions in which the reason of nullity is found in the infringement of the requirement of a valid cause of contract. Even in the rare cases, in which such contracts are not considered invalid, their legal effect is rendered equal to the effect of the pledge. The question of admissibility of fiduciary transfer of property as collateral is thoroughly discussed in the literature. The majority, under the influence of Dragoljub Aranđelović, claim that such a contract is valid, on the one hand, since it does not infringe upon any statutory prohibition, nor is it contrary to public policy or morals. On the other hand, it is also expedient, since it provides greater security for the creditor than the pledge. A contrary standpoint is taken by Andria Gams, who emphasized that European civil law is characteristic of conformity of economic purpose and legal form of legal institutions, that fiduciary transfer of property is contrary to, hence contemporary law should part with it. The author of this paper asserts that the positive attitude of Serbian doctrine towards the fiduciary transfer of property emerged in the era in which the legal necessity of pledging chattel without the transfer of its possession was not satisfactorily solved. He opines that by adopting the Law on Chattel Mortgage in 2003 ceases the otherwise legitimate need to regulate by statute the fiduciary transfer of property as collateral or to have it recognized in the case law. However, it seems reasonable to regulate, as a general legal institution, the other main type of fiduciary contracts, the fiduciary transfer of property for the purpose of managing other’s assets, that is the institution of trust. In this respect, the contemporary notion of trust from common law seems to be an appropriate general model to follow, with some reasonable adjustments to the principles of civil law, naturally. Trust has proved its merits in common law to such an extent that, regardless of serious conceptual differences between common law and civil law, some recent projects for the development of civil law have proposed model rules by which it could be transposed into European civil law, therefore into Serbian law as well.